"A Study on Online Food delivery services during the COVID -19 in Mumbai" - Prof Upendra More, Prof Ria Patnai, Prof Reema Shah, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The entire world is facing the pandemic second wave this disease has captured the entire globe. All the economies in the world is facing the financial crisis. This disease has made to follow lot of restriction in our normal life. We have to follow certain hygiene norms and need to protect our self need to follow the social distancing which has got limitations on travel which has got restricting on all sectors of industries. The public places are also under restrictions. If in case you get the disease will have to be under home quarantine or to be hospitalized in the case if the disease is severe in nature. The pandemic has created the urgency for need of medical equipment and drugs to cure from this disease. But when we discuss about the food industry it has changed its model and online deliveries for food and grocery is becoming a new normal. Which was to be purchased offline or by physically visiting the respective stores. This paper is going to discuss about the impact of Covid on the food delivery industry. It will try to throw some light on the how the economy is in a bad shape because of the pandemic. The shopping happens online as well as offline but online is getting preference. The author has used the primary as well as secondary source of data to get the complete clarity of the problem in the online Food Delivery services.